2013
DOI: 10.1021/jf303319h
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cloning and Enzymatic Characterization of an Alkali-Tolerant Endo-1,4-β-mannanase from Rhizomucor miehei

Abstract: An endo-1,4-β-mannanase gene (RmMan5A) was cloned from the thermophilic fungus Rhizomucor miehei for the first time and expressed in Escherichia coli . The gene had an open reading frame of 1330 bp encoding 378 amino acids and contained four introns. It displayed the highest amino acid sequence identity (42%) with the endo-1,4-β-mannanases from glycoside hydrolase family 5. The purified enzyme was a monomer of 43 kDa. RmMan5A displayed maximum activity at 55 °C and an optimal pH of 7.0. It was thermostable up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
4
37
0
1
Order By: Relevance
“…For most fungal endo-1,4-β-mannanases the optimal temperature and pH are between 40-70°C and pH 4.0-6.0, respectively [25], such as endo-1,4-β-mannanase from Rhizomucor miehei (optimal temperature 55°C and pH 7.0) [26], MANI and MANII from Aspergillus fumigatus IMI 385708 (60°C and pH 4.5) [27], endo-1,4-β-mannanase from P. oxalicum SO (60°C and pH 5.0) [28], endo-1,4-β-mannanase from A. niger BK01 (80°C and pH 4.5) [5], and rMan5C1 from P. pinophilum C1 (70°C and pH 4.0) [16]. However, the rPoMan5A possesses some superior properties compared to these fungal endo-1,4-β-mannanases, such as a long half-life (58 h) at high temperatures (60°C) and a wide range of pH adaptability (pH 2.0-7.0) and stability (pH 3.0-7.0).…”
Section: Discussionmentioning
confidence: 99%
“…For most fungal endo-1,4-β-mannanases the optimal temperature and pH are between 40-70°C and pH 4.0-6.0, respectively [25], such as endo-1,4-β-mannanase from Rhizomucor miehei (optimal temperature 55°C and pH 7.0) [26], MANI and MANII from Aspergillus fumigatus IMI 385708 (60°C and pH 4.5) [27], endo-1,4-β-mannanase from P. oxalicum SO (60°C and pH 5.0) [28], endo-1,4-β-mannanase from A. niger BK01 (80°C and pH 4.5) [5], and rMan5C1 from P. pinophilum C1 (70°C and pH 4.0) [16]. However, the rPoMan5A possesses some superior properties compared to these fungal endo-1,4-β-mannanases, such as a long half-life (58 h) at high temperatures (60°C) and a wide range of pH adaptability (pH 2.0-7.0) and stability (pH 3.0-7.0).…”
Section: Discussionmentioning
confidence: 99%
“…18) Recombinant β-mannanase from A. niger yields mannobiose and other mannnooligosaccharides as major and minor products, respectively. 19) Although transglycosylation by fungal β-mannanase has been reported, 20,21) those by bacteria has rarely been reported. 22) We have recently isolated several marine bacteria from seawater at the seashore of Kanazawa Port in Japan.…”
Section: )mentioning
confidence: 99%
“…Until now, the thermophilic fungi Talaromyces leycettanus JCM12802 (Wang et al, 2014a), Aspergillus fumigatus IMI 385708 (Duruksu, Ozturk, Biely, Bakir, & Ogel, 2009), Aspergillus nidulans XZ3 (Lu et al, 2014), Humicola insolens Y1 (Luo et al, 2012), Thielavia arenaria XZ7 (Lu et al, 2013), and Rhizomucor miehei (Katrolia et al, 2013) have been reported be the ideal microbial sources of excellent b-mannanases.…”
Section: Introductionmentioning
confidence: 99%